Urinary Tract Infection and Antimicrobial Susceptibility of Bacterial Isolates in Saint Joseph Kitgum Hospital, Kitgum, Uganda - Félix Carrasco Calzada; John Jairo Aguilera-Correa; Juan Cuadros González; Jaime Esteban Moreno; David Roca Biosca; Ramón Pérez-Tanoira (MDPI AG, 2022)
A cross-sectional study of microorganisms isolated from mid-stream urine samples obtained from 139 patients with suspected urinary tract infection (UTI) who presented leukocyturia was conducted from April to June 2019 at Saint Joseph Kitgum Hospital (Uganda). All microorganisms were identified by MALDI-TOF mass spectrometry in a laboratory in Spain. Antimicrobial susceptibility was determined on site using the disc diffusion method (Kirby-Bauer test) and these results were subsequently compared with those obtained in Spain using the Becton Dickinson Phoenix M50 device. The overall prevalence of UTI with bacterial growth was 64.0% (n = 89) (95% CI, 56.1-72.0), and 11 presented mixed infection. As a result, 100 microorganisms were isolated. The most common uropathogens were Enterococcus spp. (57%) and Escherichia coli (28%). Nitrofurantoin was the most effective drug (81.7% in Gram-positive and 87.3% in Gram-negative bacteria), followed by imipenem (94.2% and 74.5%, respectively). The highest resistance rates were observed for amoxicillin and ciprofloxacin (66.2% and 44.6%, respectively). Given the increasing trend toward antibiotic resistance, there is a need for bacteriological cultures and continuous surveillance of uropathogen antibiotic susceptibility. Use of amoxicillin and ciprofloxacin as empirical treatments for UTIs should be discontinued in Uganda. The findings of this study may be useful for clinicians, as they may improve empirical treatment.